2020
DOI: 10.1109/access.2020.3022770
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Feature Extraction for Centrifugal Pump Fault Diagnosis

Abstract: Raw statistical features can imitate the amplitude, average, energy and time, and frequency series distribution of a raw vibration signal. However, these raw statistical features are either not very sensitive to weak incipient faults or are unsuitable for more severe faults, thus affecting the fault detection and classification accuracy. To tackle this problem, this paper proposes a discriminant feature extraction method for Centrifugal Pump (CP) fault diagnosis. In order to obtain the discriminant feature poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…For dataset 1 (pressure 3.0 bar), it can be observed that the CWT coefficients possess large magnitudes at lower frequency scales and the energy of vibration signal is mainly concentrated around the lower frequency regions, when the vibration signal is in healthy condition. For the MSH and MSS types fault, the in-plane torsional vibrations and out-plane lateral vibrations produce additional frequency modes into the vibration signals [57]. Thus, the energy of the vibration signal spreads across the different frequency scales in the CWTS plots, ranging from low to high.…”
Section: Experimental Verification -Results and Discussionmentioning
confidence: 99%
“…For dataset 1 (pressure 3.0 bar), it can be observed that the CWT coefficients possess large magnitudes at lower frequency scales and the energy of vibration signal is mainly concentrated around the lower frequency regions, when the vibration signal is in healthy condition. For the MSH and MSS types fault, the in-plane torsional vibrations and out-plane lateral vibrations produce additional frequency modes into the vibration signals [57]. Thus, the energy of the vibration signal spreads across the different frequency scales in the CWTS plots, ranging from low to high.…”
Section: Experimental Verification -Results and Discussionmentioning
confidence: 99%
“…The SVM algorithm works based on the concept of statistical learning theory, and in multi-class classification problems, an SVM is one of the best performing machine learning algorithms. Many researchers have utilized and suggested SVMs for distinct real-life applications such as a system fault diagnosis or abnormality detection and the monitoring of patients [ [160] , [161] , [162] , [163] ]. The SVM algorithm generates a hyperplane or linear line as a decision boundary to separate different types of data points for classification tasks.…”
Section: Machine Learning For Detection Of Covid-19 Symptomsmentioning
confidence: 99%
“…In the past, ML-based approaches have been effectively used on a variety of classification problems [52][53][54][55][56]. We used a deep learning-based scheme called ResNet in this work to identify different human activities and detect falling using the generated spectrograms.…”
Section: Residual Neural Network (Resnet) For Classificationmentioning
confidence: 99%